Unveiling heterogeneity of hysteresis in perovskite thin films - Zou, Zhouyiao; Qiu, Haian; Shao, Zhibin (Discover nano, 2024)
The phenomenon of current–voltage hysteresis observed in perovskite-based optoelectronic devices is a critical issue that complicates the accurate assessment of device parameters, thereby impacting performance and applicability. Despite extensive research efforts aimed at deciphering the origins of hysteresis, its underlying causes remain a subject of considerable debate. By employing nanoscale investigations to elucidate the relationship between hysteresis and morphological characteristics, this study offers a detailed exploration of photocurrent–voltage hysteresis at the nanoscale within perovskite optoelectronic devices. Through the meticulous analysis of localized I – V curve arrays, our research identifies two principal hysteresis descriptors, uncovering a predominantly inverted hysteresis pattern in 87% of the locations examined. This pattern is primarily attributed to the energetic barrier encountered at the interface between the probe and the perovskite material. Our findings underscore the pronounced heterogeneity and grain-dependent variability inherent in hysteresis behavior, evidenced by an average Hysteresis Index value of 0.24. The investigation suggests that the localized hysteresis phenomena cannot be exclusively attributed to either photocharge collection processes or organic cation migration at grain boundaries. Instead, it appears significantly influenced by localized surface trap states, which play a pivotal role in modulating electron and hole current dynamics. By identifying the key factors contributing to hysteresis, such as localized surface trap states and their influence on electron and hole current dynamics, our findings pave the way for targeted strategies to mitigate these effects. This includes the development of novel materials and device architectures designed to minimize energy barriers and enhance charge carrier mobility, thereby improving device performance and longevity. This breakthrough in understanding the microscale mechanisms of hysteresis underscores the critical importance of surface/interface defect trap passivation in mitigating hysteretic effects, offering new pathways for enhancing the performance of perovskite solar cells.